On The Flexophotovoltaic Effect In Semiconductor P-N-Structures - et. al., R.Aliev, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, the first experimentally discovered effect of flexophotovoltaics (FPV) in silicon p-n-structures under the influence of local mechanical stress on the frontal surface is theoretically substantiated.. The regularities of the manifestation of the FPV effect are determined depending on the magnitude of the local pressure force and the intensity of photoexcitation.. Statistical processing of the experimental data by the least squares method was carried out and a new empirical formula was obtained for the experimentally determined dependence of the short circuit photocurrent of a silicon structure on the local mechanical stress.